NEGATIVE TRANSFER FROM L1 INTO FL PRONUNCIATION - Erick, Chrysostomus; Sudarsono, Sudarsono; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe present study deal with the students' errors in pronouncing English words made by the seventh grade of students of SMP Gembala Baik Pontianak in the academic year 2017-2018. The researcher is interested in conducting research of Teochew transferred in pronouncing English words because the student still have interference in pronunciation, therefore the result of the research can be used as a feedback for the teacher and student's improvement. The data required for the study were collected by (1) Observation, (2) Test, and (3) audio recording. Finally, the result of the analysis shows that there are three kinds of errors made by the subjects, There are lengthening sounds (39,22%) and substitutions sounds (60,78%). To solve the students' pronunciation errors, they need a lot of drills and practices to pronounce English using IPA by watching carefully how the native speaker produce the sounds correctly. It is suggested that teachers should pay more attention to those particular sounds and provide extra exercise to the learnersKeywords: Pronunciation transfer, lengthening sounds, substitution sound, Teochew students